Feminism and Contemporary Indian Women's Writing - Jackson, E. author. aut Link
IX, 200 p.
Keywords: This book is a comparative and developmental study of the expression of feminist concerns in the novels of Kamala Markandaya, Nayantara Sahgal, Anita Desai, and Shashi Deshpande, among the best known and most prolific Indian novelists writing in English, who have been self-consciously engaged with women's issues during the postcolonial era.